2000
DOI: 10.1007/bf02494670
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hydrophobic amines on hydrolysis of bis(p-nitrophenyl) methylphosphonate in micellar solutions of cetylpyridinium bromide

Abstract: The kinetics of hydrolysis of bis (p-nitrophenyl] methylphosphonate in the presence of prima/3' aliphatic amines in aqueous micellar solutions of cetylpyridinium bromide was studied. Tile reaction proceeds via tv, o routes, alkaline hydrolysis and amine-catalyzed hydrolysis according to the general basic catalysis mechanism. The contributions of these routes and the catalytic effect of mieelles depend on the hydrophobicity of the amines. The formation of different types of miceltes was found, and their charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The distribution of water in the system is important for different hydrolytic reactions. For example, earlier we found that the water content in the microemulsion interface influences the rate of ester hydrolytic destruction [11].…”
Section: 10il-in-water Microemulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of water in the system is important for different hydrolytic reactions. For example, earlier we found that the water content in the microemulsion interface influences the rate of ester hydrolytic destruction [11].…”
Section: 10il-in-water Microemulsionmentioning
confidence: 99%
“…Earlier we have studied the kinetic properties of primary aliphatic amines in various self-organized solutions and have discussed the peculiarities of microemulsion influence on the rate and mechanism of nucleophilic substitution processes [10,11]. However, the presence of reactants in the system can produce structural changes in the microemulsion medium and the aim of this study is to reveal the influence of primary long-chain amines on the structural properties of microemulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the critical micelle concentration (CMC) of decylamine was reported to be 9.5 × 10 −4 M for nonprotonated from 2.7 × 10 −3 M for 75% protonation, while fully protonated form apparently does not form micelles. 61 There is no experimental data on the effect of salt on the CMC of decylamine, but the CMC of a slightly longer surfactant dodecyldimethylammonium chloride was found to be 16.2 times lower in 1 M NaCl solution than in neat water. 62 Still, it seems reasonable to assume that decylamine does not form micelles at pH 3.7 and 9.3 and may behave similarly to DTAB, with regard to surface adsorption on polyamide.…”
Section: Methodsmentioning
confidence: 99%
“…As emphasized by Mirgorodskaya and his colleagues in their work they showed that Critical Micellar Concentration (CMC) of chloride primary alkyl amines (chloride salt of Decyl and Octyl amine) depend on protonation degree of head group. They conclude that as the percentage of protonation increase, the concentration needs to form micelles also increase (Mirgorodskaya et al, 2000). Table summarized CMC values for chloride salt of Decylamine and Octadecylamine depending on protonation degree of amine head (Table 1).…”
Section: As Surfactant Unit Producing Micellar Aggregatementioning
confidence: 99%